Interracial Communication at Dinner Parties in Rebeck and Gersten-Vassilaros’ Omnium Gatherum and Akhtar’s Disgraced - Ali Flefil Al-Hussainawy, Ansam (International Journal of Psychosocial Rehabilitation, 2020)
This study deals with interracial debate that occurs at dinner parties in two post-9/11 American plays, namely, Teresa Rebeck and Alexandra Gersten-Vassilaros’ Omnium Gatherum (2004) and Akhtar’s Disgraced (2011) respectively. Interracial communication, here, means the controversy about different topics and issues that happens between/among individuals of different races and cultures; each one is trying to support his/her viewpoint whether it is right or wrong. The setting in which such argument occurs is dinner parties in a post- 9/11 era. Accordingly, the aim of this study is to shed light on using dinner parties in literary works, drama in particular, to discuss various issues in a form of interracial altercations that end with aggressive attitudes among characters. The focus is on two sample plays: Omnium Gatherum and Disgraced. Structurally, the work starts with an introduction that illustrates the meaning of interracial communication, dinner parties in literature, and a hint on post-9/11 American drama. Then, the two chosen plays are analyzed in terms of the mentioned theme. The conclusion sums up the findings of this research. This includes that: (1) dinner parties are used as a device to present different attitudes and issues. (2) The characters of guests are depicted from different races, cultures, and tendencies. (3) The debate turns around different subjects and each guest tries to display his/her viewpoint with a strong defense. (4) Parties of this type often end negatively with a quarrel. (5) The two selected plays are the epitome of this type of invitations.